2013
DOI: 10.1021/cb400335k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Substrate Selectivity Motif in Amino Acid Decarboxylases Unveils a Taurine Biosynthesis Pathway in Prokaryotes

Abstract: Taurine, the most abundant free amino acid in mammals, with many critical roles such as neuronal development, had so far only been reported to be synthetized in eukaryotes. Taurine is the major product of cysteine metabolism in mammals, and its biosynthetic pathway consists of cysteine dioxygenase and cysteine sulfinic acid decarboxylase (hCSAD). Sequence, structural, and mutational analyses of the structurally and sequentially related hCSAD and human glutamic acid decarboxylase (hGAD) enzymes revealed a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Taurine can be derived from Cys via the activities of Cys dioxygenase and Cys sulfinic acid decarboxylase in phytoplankton cells (Tevatia et al, 2015). Alternatively, taurine may be produced from cysteate via a decarboxylation step (Agnello et al, 2013). Taurine can then be degraded by taurine dioxygenase (tauD) into either aminoacetaldehyde plus sulfite or sulfoacetaldehyde (Figure 2) (Van der Ploeg et al, 1996).…”
Section: Sulfonate Metabolismsmentioning
confidence: 99%
“…Taurine can be derived from Cys via the activities of Cys dioxygenase and Cys sulfinic acid decarboxylase in phytoplankton cells (Tevatia et al, 2015). Alternatively, taurine may be produced from cysteate via a decarboxylation step (Agnello et al, 2013). Taurine can then be degraded by taurine dioxygenase (tauD) into either aminoacetaldehyde plus sulfite or sulfoacetaldehyde (Figure 2) (Van der Ploeg et al, 1996).…”
Section: Sulfonate Metabolismsmentioning
confidence: 99%
“…The CDO/CSAD pathway is found in animals [1][2][3][4][5]; the Serine/Sulfate pathway is found in developing chick embryos [6], chick liver [7], and microalgae (present study); the XDH/Xsc pathway is found in bacteria [8,9].…”
Section: Figurementioning
confidence: 75%
“…Cysteate is then decarboxylated to form taurine [7]. Bacterial taurine synthesis remains unclear though exogenous cysteine sulfinic acid supplementation enables accumulation of intracellular taurine indicating the presence of a CSAD homolog [8]. In many bacteria, taurine catabolism involves deamination of taurine to sulfoacetaldehyde followed by desulfonation producing acetylphosphate and sulfite [9].…”
Section: Introductionmentioning
confidence: 99%
“…Upon cysteine stimulation, CDO forms the intramolecular Cys-Tyr cofactor (mature form), which appeared as a lower band in SDS-PAGE compared to the form without cofactor (immature form) 14 . The formation of Cys-Tyr cofactor could increase the catalytic efficiency by approximately 10 fold over the cofactor-free CDO 32 , which is critical in maintaining cysteine concentration below toxic levels 33 . In this study, fish CDOs were transfected into HepG2 cells, which contained no endogenous CDO activity 34 , thus provided a clean background for CDO activity measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Taurine biosynthesis is controlled by two key enzymes, CDO and CSD 8 . To date, CDO and CSD have been identified and characterized from mammals to eubacteria 32 35 36 37 38 , suggesting the taurine biosynthesis pathway via CDO and CSD is highly conserved during evolution. Given the fact that taurine biosynthesis ability varies greatly among species, it will be interesting to examine whether the regulation of CDO and CSD can be different among species.…”
Section: Discussionmentioning
confidence: 99%